The influence of aerobic capacity on anaerobic performance and recovery indices in basketball players - Hoffman, J. R.; Epstein, S.; Einbinder, M.; Weinstein, Y. (The Journal of Strength and Conditioning Research, 1999)
This study examined the effect of aerobic capacity on performance, fatigue, and heart rate recovery following high-intensity anaerobic exercise in national-level basketball players. Twenty subjects (19.0 ± 1.7 years, 88.4 ± 8.0 kg, 194.2 ± 6.0 cm, 50.2 ± 3.8 ml·kg·min1) participated in this investigation. Each subject performed a treadmill test to determine maximal oxygen consumption (o2max), a Wingate Anaerobic Power Test (WAnT), and a field test of anaerobic power common to basketball players (line drill). The line drill is a continuous 143-m sprint with several changes of direction. The line drill was performed 3 times (T1, T2, and T3) with a 2-minute passive rest between each sprint. A moderate correlation was seen between o2max and mean power of the WAnT (r = 0.57). However, no significant relationship was observed between o2max and the fatigue index in either the WAnT (r = 0.23) or line drill (r = 0.01). Little to no correlation was observed between o2max and heart rate recovery in the WAnT (r = 0.22) and line drill (r = 0.04, r = 0.19, and r = 0.30 in T1, T2, and T3, respectively). These results showed little to no relationship between aerobic capacity and recovery indices from high-intensity exercise in basketball players.